Der Umlaut im Berberischen des Djebel Nefusa in Tripolitanien - Vycichl, Werner (Annali dell'Istituto Universitario Orientale di Napoli, 1954)
Keywords: Linguistique – Djebel Nefousa

Some properties of Zuara nouns with special reference to those with consonant initial - Mitchell, Terence Frederic (Mémorial André Basset: 1895-1956, 1957)
Keywords: Linguistique – Djebel Nefousa

Long consonants in Phonology and Phonetics - Mitchell, Terence Frederic (Studies in linguistic analysis. special issue of the Philological Society, 1957)
Keywords: Linguistique – Djebel Nefousa

Particle-Noun Complexes in a Berber Dialect (Zuara) - Mitchell, Terence Frederic (Bulletin of the School of Oriental and African Studies, 1953)
‘Particle’ and ‘Noun’ are not a priori categories of universal applicability. Ad hoc definition of their ‘meaning’ is given under A. Detailed description of structural relations observable between them follows at B.
Keywords: Linguistique – Djebel Nefousa